2017
DOI: 10.1016/j.toxicon.2017.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Comparative proteomics reveals recruitment patterns of some protein families in the venoms of Cnidaria

Abstract: Cnidarians are probably the oldest group of animals to be venomous, yet our current picture of cnidarian venom evolution is highly imbalanced due to limited taxon sampling. High-throughput tandem mass spectrometry was used to determine venom composition of the scyphozoan Chrysaora lactea and two cubozoans Tamoya haplonema and Chiropsalmus quadrumanus. Protein recruitment patterns were then compared against 5 other cnidarian venom proteomes taken from the literature. A total of 28 putative toxin protein familie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
16
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 77 publications
2
16
0
3
Order By: Relevance
“…However, whether an abundance of neurotoxins is characteristic of anthozoan venom cannot be determined until the taxonomic bias in available data is addressed and knowledge of coral venoms improves. Furthermore, comparison of soluble nematocyst proteomes from eight cnidarian species indicates that approximately one third of all toxin protein families identified are present in both Anthozoa and Medusozoa, although no representative of Staurozoa was included [42]. Of the remaining toxin families, four were taxonomically restricted to a single class and 15 were absent in at least one class, and there was no correlation between toxin family absence and presence and phylogenetic relatedness [42].…”
Section: Venom Evolution Across Cnidariamentioning
confidence: 99%
See 1 more Smart Citation
“…However, whether an abundance of neurotoxins is characteristic of anthozoan venom cannot be determined until the taxonomic bias in available data is addressed and knowledge of coral venoms improves. Furthermore, comparison of soluble nematocyst proteomes from eight cnidarian species indicates that approximately one third of all toxin protein families identified are present in both Anthozoa and Medusozoa, although no representative of Staurozoa was included [42]. Of the remaining toxin families, four were taxonomically restricted to a single class and 15 were absent in at least one class, and there was no correlation between toxin family absence and presence and phylogenetic relatedness [42].…”
Section: Venom Evolution Across Cnidariamentioning
confidence: 99%
“…Furthermore, comparison of soluble nematocyst proteomes from eight cnidarian species indicates that approximately one third of all toxin protein families identified are present in both Anthozoa and Medusozoa, although no representative of Staurozoa was included [42]. Of the remaining toxin families, four were taxonomically restricted to a single class and 15 were absent in at least one class, and there was no correlation between toxin family absence and presence and phylogenetic relatedness [42]. In fact, the reported loss of numerous toxin families in Cubozoa was associated with an erroneous phylogenetic reconstruction that placed Cubozoa external to Anthozoa and Medusozoa [42].…”
Section: Venom Evolution Across Cnidariamentioning
confidence: 99%
“…Approximately 30 different varieties of nematocyst are known to exist, but individual species usually combine no more than two to six structural types that are collectively known as the organism's cnidome (Östman, ). Cnidarians are possibly the earliest diverging venomous animal lineage to deploy venom for both predation and defense (Jaimes‐Becerra et al, ). Venom production and maintenance are therefore central to cnidarian existence and evolution, and increasingly more is known about the evolutionary history and phyletic distribution of cnidarian toxins.…”
Section: Introductionmentioning
confidence: 99%
“…Venom production and maintenance are therefore central to cnidarian existence and evolution, and increasingly more is known about the evolutionary history and phyletic distribution of cnidarian toxins. A pattern is emerging which suggests venoms with predominantly cytolytic and neurotoxic activities were established by early cnidarian ancestors followed by lineage-specific recruitment of certain toxin protein families, with cytolysins diversifying prominently in Medusozoa and neurotoxins in Anthozoa (Balasubramanian et al, 2012;Brinkman et al, 2015;Huang et al, 2016;Jaimes-Becerra et al, 2017;Li et al, 2014Li et al, , 2016Macrander, Brugler, & Daly, 2015;Madio, Undheim, & King, 2017;Ponce, Brinkman, Potriquet, & Mulvenna, 2016;Rachamim et al, 2015). When an innovative unsupervised clustering approach was used to compare toxin composition between groups of venomous animals, the results revealed that despite the early divergence and morphological simplicity of cnidarians, their toxin composition was as complex as those of venomous insects, gastropods, and elapid snakes (Jaimes-Becerra et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…For example, we found that the cnidarian gastrodermal lining and mesenteries, previously termed the "endomesoderm" (Martindale et al, 2004), can be subdivided into two distinct clusters that we term digestive filaments, where prey is held and digested, and the gastrodermal lining. The gastrodermal cell cluster, including the classically described epitheliomuscular cells (Frank and Bleakney, 1976) enzymes, which might be related to digestion but also to non-cnidocyte venom functions (Jaimes-Becerra et al, 2017;Moran et al, 2013). Finally, a group of modules are constituted by not peer-reviewed) is the author/funder.…”
mentioning
confidence: 99%